Variations in water uptake pattern and soil desiccation in response to vegetation types on the western Loess Plateau in China - Hongqian Yu; Yixian Bi; Zhanjun Wang; Yingjun Zhang (Agricultural Water Management)
Understanding water uptake, soil water storage, and desiccation patterns of vegetation in northwest China’s semiarid and desert regions can manage the soil water cycle. However, the seasonal variations in plant water uptake across different vegetation types are not well understood. Here, we examined the sources of water for four vegetation types (artificial forest, alfalfa pasture, cropland, and natural grassland) using plant xylem and soil water isotopes (δ2H and δ18O) to assess the soil water storage (SWS) and desiccation within soil depths of 0–500 cm in a year. We found that artificial forest and cropland consistently absorbed water from soil depths of 100–200 cm throughout the year. The natural grassland changed from absorbing water from depths of 100–200 cm during the non-growing season to absorbing water from depths of 0–100 cm and 200–500 cm during the growing season. The alfalfa pasture absorbed water from depths of 100–200 cm during the non-growing season and from depths of 0–100 cm during the growing season. Furthermore, the alfalfa pasture had the lowest SWS of 82.61–102.64 mm within soil depths of 0–500 cm, which led to severely dry soil layers within the 100–200 cm depth interval. In contrast, the SWS values of the other three types of vegetation were all > 118.97 mm, resulting in unrecovered dry soil layers during the growing season. These results enhance our understanding of how plant water uptake influences soil water dynamics and hydrological niche segregation across the seasons.